2015
DOI: 10.13000/jfmse.2015.27.5.1508
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations of Outer Membrane Protein Genes of Vibrio harveyi Isolated in Korea and Immunogenicity of OmpW in Olive Flounder, Paralichthys olivaceus

Abstract: Vibrio harveyi is a pathogenic marine bacterium causing systemic symptoms resulting in mass mortalities in fishes and shrimps in aquaculture. Outer membrane proteins(OMPs) are related to the pathogenicity and thus good targets for diagnosis and vaccination for Gram negative bacteria. Recently vaccination strategies using the OMPs have been suggested to control vibriosis in several fish species. In this study, we have isolated V. harveyi from diseased marine fishes from different regions of Korea and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…By BITC treatment, gene expression level of VP2362 was signi cantly downregulated compared with that of control group. The outer membrane protein is virulence related (Kim MS 2015) and commonly found in Gram-negative bacteria (Xiong XP 2010). Previous ndings have con rmed that the cell surface integrity, neutralizing host defense mechanisms, cell adhesion and invasion, and inhibition of the complement system are all affected by outer membrane proteins (Koebnik R 2000).…”
Section: Discussionmentioning
confidence: 99%
“…By BITC treatment, gene expression level of VP2362 was signi cantly downregulated compared with that of control group. The outer membrane protein is virulence related (Kim MS 2015) and commonly found in Gram-negative bacteria (Xiong XP 2010). Previous ndings have con rmed that the cell surface integrity, neutralizing host defense mechanisms, cell adhesion and invasion, and inhibition of the complement system are all affected by outer membrane proteins (Koebnik R 2000).…”
Section: Discussionmentioning
confidence: 99%
“…VPA0318 encodes the outer membrane protein OmpV. Outer membrane proteins (OMPs) are widespread in Gram-negative bacteria [ 36 ] and are related to pathogenicity [ 37 ]. A previous study reported that outer membrane proteins could medicate the infection process including chemotaxis, motility through the mucous layer lining the intestinal wall, and survival of the gastric acid barrier [ 38 ].…”
Section: Discussionmentioning
confidence: 99%